Challenges, Lessons, And Directions in Transferring Health-Promoting Hospitals to Local Administrative Organizations: A Literature Review and Knowledge Synthesis - Sujimongkol, Chinakorn; Kaewsombat, Kuttiya; khunpiluek, Issara; Sarakshetrin, Atiya (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This article aimed to review the literature and synthesize knowledge about the transfer of sub-district health promoting hospitals (HPHs) to local administrative organizations (LAOs) in Thailand. It examined the background, current situation, lessons learned from pilot areas, attitudes of relevant personnel, and synthesized knowledge and policy recommendations for the transfer. The study found that the transfer of HPHs was part of the decentralization of public health, which faced many challenges and obstacles, particularly in terms of resource allocation, readiness of LAOs, and fostering participation from various sectors. However, there were several pilot areas that demonstrated success factors, including leadership, cooperation among local agencies, and restructuring of work processes. Therefore, driving the transfer of HPHs required policy clarity, capacity building of LAOs, creating understanding among personnel, and promoting integrated work in the area. This would be to ensure that the transfer would be efficient and would maximize benefits for the well-being of the population.